Approaches to locum physician recruitment and retention: a systematic review - Nathan Ferreira; Odessa McKenna; Iain R. Lamb; Alanna Campbell; Lily DeMiglio; Eliseo Orrantia (BMC, 2024)
Abstract A robust workforce of locum tenens (LT) physicians is imperative for health service stability. A systematic review was conducted to synthesize current evidence on the strategies used to facilitate the recruitment and retention of LT physicians. English articles up to October 2023 across five databases were sourced. Original studies focusing on recruitment and retention of LT's were included. An inductive content analysis was performed to identify strategies used to facilitate LT recruitment and retention. A separate grey literature review was conducted from June-July 2023. 12 studies were retained. Over half (58%) of studies were conducted in North America. Main strategies for facilitating LT recruitment and retention included financial incentives (83%), education and career factors (67%), personal facilitators (67%), clinical support and mentorship (33%), and familial considerations (25%). Identified subthemes were desire for flexible contracts (58%), increased income (33%), practice scouting (33%), and transitional employment needs (33%). Most (67%) studies reported deterrents to locum work, with professional isolation (42%) as the primary deterrent-related subtheme. Grey literature suggested national physician licensure could enhance license portability, thereby increasing the mobility of physicians across regions. Organizations employ five main LT recruitment facilitators and operationalize these in a variety of ways. Though these may be incumbent on local resources, the effectiveness of these approaches has not been evaluated. Consequently, future research should assess LT the efficacy of recruitment and retention facilitators. Notably, the majority of identified LT deterrents may be mitigated by modifying contextual factors such as improved onboarding practices.